TAWARAN STUDI AGAMA HINGGA FEMINISME BAGI ILMU HUBUNGAN INTERNASIONAL - M. Yustian Yusa; M. Yusuf Qardlawi (Sriwijaya Journal of International Relations, 2021)
This paper explored some methods and approaches in qualitative methodology in international relations research, from religious, literature, anthropology and feminism approaches. At the end, with the interdisciplinary approach that showed the prons and cons in international relations research—multi perspectives but the lost of identity epistemologically.